Recomendações para especificação de vidros em edificações comerciais na região climática de Porto Alegre - RS - Cornetet, Mariângela Conte (2009)
In business buildings, great part of the required power is spent on the air conditioning of internal settings. The transparent façades on such buildings are greatly significant on such matters, since a notable percentage of the thermal exchanges happen trough these elements. This paper structures an overview on the historical changes on the use of glasses on business buildings in the city of Porto Alegre, state of Rio Grande do Sul, highlighting the contemplation of the aspect of thermal and luminosity control on built environments. For each historical period, it s notable that the availability of different types of glasses on the market, chosen by architects, changes, resulting in diverse thermo-environmental and visual behaviors. The present paper was based on historical data, ranging from the period of 1992 to 2008, allowing analyses based on the performance of each alternative, taking into consideration the glasses spectrophotometric characteristics, solar factor values, visible transmission and thermal transmittance and the relation within the amount of energy required for cooling and heating the considered settings. 25 buildings were analyzed in the city and, from those, seven were selected for being considered to be representative of their period, with different solutions on their glass coverings. The data obtained was the basis for comparing their performances, on the various solar orientations, with that of a common glass. A trend of specifying lenses less reflective has been observed, with an increase in the amount of energy inflowing the rooms; and insulated glasses also, that hamper trade among environments.